The Effect of Motivation, Workload, Subjective Norms, and Skills of the Accuracy of Triage Implementation to IGD Nurses in Karo Regency - Sahat Tua Naiboha, Beres; Kusumawati, Prima Dewi; Novita Ana Anggraini (STRADA : Jurnal Ilmiah Kesehatan, 2025)
Priority of patient handling can be done by using triage. The triage system greatly influences the success rate of assistance when the patient experiences an emergency . The aim of the study was to analyze influence between motivation, burden work, and subjective norms to accuracy implementation triage to IGD nurses in karo district. The research design used was analysis descriptive with approach cross sectional. Population study all Emergency Nurses in Karo Regency. The research sample was 101 using the Stratified Sampling technique. The research was conducted in May 2024. Data analysis used multiple linear regression statistical tests . The results of the study show motivation of 0,000, the load Work of 0.022, subjective norm of 0.015 and triage skills of 0.000.